Dark diversity and habitat conservation status: Two sides of the same coin for conservation and restoration? - Simon Chollet; Mathilde Dano; Gabrielle Thiébaut; Vincent Jung (Ecological Indicators)
The current biodiversity crisis calls for an acceleration in the implementation of measures to conserve and restore ecosystems around the world. To achieve these objectives, it is imperative to provide scientifically robust tools that practitioners can easily apply. In recent years, two theoretical frameworks have been proposed, habitat-specific species pools and dark diversity. The aim of our study is to assess the value of combining these two concepts in order to improve predictions of dark diversity by restricting estimates to the pool of species typical of the habitat. Our study focuses on two habitats, heathlands and grasslands, both of which present major conservation and restoration challenges. We carried out vegetation surveys in 290 heathlands and 425 grasslands spread throughout the region. Our results indicate that restricting dark diversity estimates to the habitat-specific species pool significantly reduces the number of species estimated in dark diversity. Furthermore, we show that a large proportion of the species predicted in the dark diversity are species nontypical of the studied habitats. Our results also demonstrate that there is no redundancy between approaches based on the assessment of observed conservation status and those based on dark diversity. The use of the dark diversity is complementary to approach based on the assessment of observed conservation status for the diagnosis, prioritisation and monitoring of conservation or restoration measures. Nevertheless, our results indicate that in the context of conservation and restoration, estimates of dark diversity must be restricted to the habitat-specific species pool.